2018
DOI: 10.1051/e3sconf/20187002004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of forced convection of water/EG-Al2O3 nanofluids inside horizontal tube

Abstract: In this paper, forced convection of water/EG-Al2O3 nanofluids inside horizontal stainless steel tube is studied experimentally. As base fluid served water/EG mixture of two ratios (60:50 and 50:50). Nanoparticle mass concentrations was 0.1% or and 1%. Transition and turbulent flow regimes were tested. Average heat transfer coefficient and pressure drop values were determined for nanofluids and compared to base fluids. Deterioration of heat transfer for all tested nanofluids has been recorded compared to base f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Sundararaj et al [144] found that the Nu number and HTC coefficient significantly increased with the increase in NPs concentration, and for the maximum tested concentration and the highest Re number, the HTC increase was about 16.3% and for turbulent flow. Cieśli ński and Kozak [145] observed a decrease in the Nu number with increasing concentration of NPs up to 25% for the same Re number. Ho et al [146] observed no increase in the Nu number compared to base fluid with a significant increase in the concentration of NPs.…”
Section: Characteristics Of the Conducted Researchmentioning
confidence: 90%
“…Sundararaj et al [144] found that the Nu number and HTC coefficient significantly increased with the increase in NPs concentration, and for the maximum tested concentration and the highest Re number, the HTC increase was about 16.3% and for turbulent flow. Cieśli ński and Kozak [145] observed a decrease in the Nu number with increasing concentration of NPs up to 25% for the same Re number. Ho et al [146] observed no increase in the Nu number compared to base fluid with a significant increase in the concentration of NPs.…”
Section: Characteristics Of the Conducted Researchmentioning
confidence: 90%